2015
DOI: 10.4103/2229-5151.170840
|View full text |Cite
|
Sign up to set email alerts
|

Complications during intrahospital transport of critically ill patients: Focus on risk identification and prevention

Abstract: Intrahospital transportation of critically ill patients is associated with significant complications. In order to reduce overall risk to the patient, such transports should well organized, efficient, and accompanied by the proper monitoring, equipment, and personnel. Protocols and guidelines for patient transfers should be utilized universally across all healthcare facilities. Care delivered during transport and at the site of diagnostic testing or procedure should be equivalent to the level of care provided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 63 publications
1
35
0
1
Order By: Relevance
“…Many international guidelines and recommendations focus on the transfer of critically ill patients. [16][17][18] These guidelines have the same aim: to improve the quality of transport thereby decreasing AEs. Most of these recommendations focus on the transfer of critically ill patients already admitted to the ICU, being transferred to and from ICU, by ICU trained personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Many international guidelines and recommendations focus on the transfer of critically ill patients. [16][17][18] These guidelines have the same aim: to improve the quality of transport thereby decreasing AEs. Most of these recommendations focus on the transfer of critically ill patients already admitted to the ICU, being transferred to and from ICU, by ICU trained personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Because this study was a retrospective review, we focused on the definite outcome of CPA to reduce bias. Additionally, previous studies [5, 7, 8, 26, 27] have evaluated the outcome data of patients who were transported, and reported that AEs such as arterial blood gas changes, physiologic changes, and equipment-related problems are frequent. Fourth, we did not compare CPA rates before and after implementation of RRT accompanied transport to determine whether accompaniment by a specialized team such as the RRT can reduce AEs during IHT.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of distribution of commonly used sedation agents such as fentanyl, propofol, and midazolam is increased, and much higher than normal doses are often required to achieve sedation goals [12]. Furthermore, after continuous infusions of such agents are discontinued, sequestered drug is released back into the plasma, which prolongs sedation in an unpredictable manner [13]. Importantly, changes to the circuit, such as replacing a clogged filter or oxygenator, can reset this process in unpredictable ways.…”
Section: Sedationmentioning
confidence: 99%
“…As such, patients must be transported to a stationary CT scanner in many cases. Similar to other critically ill patients, this requires substantial staffing resources and time to achieve [ 14 ]. The skillsets of multiple providers are required including bedside nurses, respiratory therapists, perfusionists/ECMO specialists, and sometimes physicians.…”
Section: Implications Of Ecmo On Diagnosis and Treatment Of Neurologimentioning
confidence: 99%